Aplikasi Penjualan Tiket Kelas Pelatihan Berbasis Mobile menggunakan Flutter - Filian Enggar Krisnada; Radius Tanone (Jurnal Teknik Informatika dan Sistem Informasi, 2019)
Abstract — Pincher is an online platform that is useful for assisting in finding and registering for training classes aimed at facilitating users who want to find their identity and channel their talents and inspirations creatively. This pincher application provides information and distributes training classes by selling class tickets. In its development as an online platform, Pincher still uses the website as a means of distributing training classes owned by Pincher, so this tool is less effective and efficient for users because the Pincher website is too complicated to access using a mobile phone or smartphone. Therefore, to help users access the Pincher application using their mobile phones, Pincher applications are made in a simple form that is applied to mobile applications. In addition, Pincher also does not have a feature that can make it easier for customers to determine the class to be chosen. Therefore this mobile application will be equipped with a system that can make it easier for users to choose attractive classes for customers, namely with a recommendation system. Keywords— Ticket Selling Application, Flutter, Mobile Application, Recommendation System.